Propriedades tensiométricas do peritônio da paca (cuniculus paca) a fresco e conservado em glicerina 98% - Camargo, Angela Daniele [UNESP]; Camargo, Paulo César; Leal, Leonardo Martins [UNESP]; Garcia Filho, Sérgio Pinter [UNESP]; Martins, Leandro Luís [UNESP]; Shimano, Antônio Carlos; Machado, Márcia Rita Fernandes [UNESP] (FapUNIFESP (SciELO), 2014)
In constant searching for alternative biological material to perform implants and new options of experimental animal models, the objective of this investigation was to describe the mechanical properties of the peritoneum paca (Cuniculus paca Linnaeus, 1766) fresh and preserved in 98% glycerin. Samples of fresh and preserved in glycerin for periods of 30, 60 and 90 days were subjected to mechanical tests. Four adult animals, male or female, with mean body weight of eight kilograms, were used for collecting samples of the peritoneum. All tissues preserved in glycerin 98% showed a decrease in stiffness and increase in ductility and toughness. Considering the maximum force applied to the peritoneum, significant increase was observed in values (p<0.01) of samples stored for 60 and 90 days when compared to fresh material. In relation to the stretch variable, an increase was observed in all storage time of glycerin samples, verifying significant difference (p<0,01) when compared with the fresh samples. The variable area also showed significance (p <0.01) between the values of the fresh samples (5.40 mm2) and preserved in the glycerin by periods of 30 days (4.50 mm2), 60 days (9.00 mm2) and 90 days (7.20 mm2), thus indicating that the area of this membrane increased by 0.033 mm2 per day. Generally, it was concluded that the 98% glycerin is a substance effective for the preservation of the peritoneum of the agouti paca, therefore improves its mechanical properties allowing the support membranes greater deformation forces. Thus, the results obtained in mechanical tests of the peritoneum of paca suggest its use as an alternative biological material.
Tensiometer peritoneum properties of the paca (Cuniculus paca) fresh and preserved in glycerin 98%
Keywords: Biological membranes; Cuniculus paca; Mechanical tests; Paca; Peritoneum; Reconstruction; Surgery